Hijrah anak Punk pada Komunitas Bikers Subuhan Kotamobagu - Mustamin, Kamaruddin; Macpal, Sunandar; Maulasa, Aisma (Farabi, 2022)
Street children, including punk youth, are often associated with negative social stigmas such as delinquency, deviance, and public disorder. However, this generalization does not fully capture the lived experiences of punk youth, particularly those involved in the Bikers Subuhan Community in Kotamobagu. This study aims to examine the hijrah process, the factors motivating it, and the transformation of religious behavior among punk youth after joining the community. Employing a qualitative method with a phenomenological approach, this research focuses on the subjective experiences and meanings constructed by the participants. Data were collected through in-depth interviews, participant observation, and documentation, involving former punk youth as primary informants, as well as community leaders and residents as supporting informants. The findings reveal that hijrah is understood as a multilayered and ongoing spiritual transformation, encompassing i‘tiqadiyah hijrah (realignment of faith and intention), fikriyah hijrah (transformation of mindset), syu‘uriyyah hijrah (shifts in preferences and lifestyles), and sulukiyyah hijrah (moral and behavioral transformation). This process unfolds gradually through personal experiences, emotional struggles, and strong community support. Analysis based on Max Weber’s theory of social action indicates that post-hijrah behavioral changes are shaped by the interplay of instrumental rationality, value-oriented rationality, traditional action, and affective action. The study concludes that hijrah among marginalized groups is not merely a symbolic change but a profound reconstruction of identity, life orientation, and social relations, contributing to the strengthening of religious commitment and community solidarity.